A NOVEL APPROACH FOR OPTIMAL DESIGN OF WATER DISTRIBUTION NETWORKS - Van Tinh, Pham; Van Thanh, Dang; Quoc Nam, Giang (Journal of Forestry Science and Technology, 2016)
A water distribution network consists of pipes, reservoirs, pumps, tanks, and other hydraulic components. The main purpose of a water distribution network is to provide reliable service to the individual customers in the required quantity and at sufficient pressure. Nearly 80% to 85% of the cost of a water supply project is used in the distribution network; therefore, using reasonable methods for designing a water distribution system will result in considerable savings. In this paper, we introduce a novel simulation-based optimization method, CMAESEP, which couples the Covariance Matrix Adaptation Evolution Strategy Optimization Algorithm and the Epanet hydraulic simulator for optimal designing water distribution networks. The proposed method is applied to the published benchmark water network of Hanoi. The result shows that the new method is able to identify the best solution and is promising method for a further development of the design of complex water distribution network.